Subchronic toxicity study of standardized methanolic extract of Mitragyna speciosa Korth in Sprague-Dawley Rats - Ilmie, Mohd U.; Jaafar, Hasnan; Mansor, Sharif M.; Abdullah, Jafri M. (Frontiers in Neuroscience, 2015)
Mitragyna speciosa Korth, or better known as ketum, has long been used by traditional folk around Southeast Asia to prevent fatigue from working under hot tropical weather and as a replacement of opium, which can then cause addiction. To date, no findings have been reported of the toxic effect of ketum subchronically (28 days). Hence, the aim of this study was to investigate the toxicity of subchronic effect of standardised methanolic extract of ketum (SMEMS) in Sprague-Dawley rats. Rats were orally administered with 100, 200, and 500 mg/kg of SMEMS for 28 days. Body weights were recorded daily. They were terminated at day 28 to obtain data for haematology, biochemistry, and histopathology of the brain, liver, kidney, lung, heart, sciatic nerve, and spinal cord. The SMEMS affected body weight compared to control group. Biochemistry findings showed that liver and kidney were affected with the abnormal values in AST, creatinine, globulin, glucose, total protein, and urea. However, SMEMS produced toxic effect more to liver, kidney, and lung than other organs as observed histopathologically. The results suggested subchronic exposure of ketum is toxic to the physiology of the animals.